Weather Inflections - Louie, Joel; Andruszkiewicz, J.; Mather, Bryan.; Raxworthy, Kevin; Thomas, Paul (National Art Museum of China, 2011)
Weather Inflections explores issues embedded within the philosophical landscape of phenomenology. Specifically it looks at how we, as embodied beings, experience changing weather patterns in our environment. In facilitating a temporary rupture in an individual’s perceptual framework, the Weather Inflections installation seeks to expand the vocabulary of awareness of its audience and challenge established paradigms of sensory cognizance. By ‘crossing the perceptual wires’ and initiating a synaesthetic experience, an individual may observe spatially and temporally mapped digital data within their physical self as manifested by a tactile and aural experience of weather from elsewhere. This interactive installation further explores notions of embodied interaction through the lens of phenomenology by expressing our interactional relationship with computer data and its mediation of the experience of the climate / environment. As embodied beings, our physical reality is that while we may be able to acutely sense weather changes in the present moment, it is much more difficult to recall and make accurate comparisons between sensory perceptions across different spatial-temporal mappings. Weather Inflections aims to help bridge this perceptual gap by allowing users to have an immediate tactile sonic experience of changes in climate data analogous to Perth Western Australia. In addition to providing a novel, visceral representation of the data, this approach may also help an individual literally ‘internalize’ the experience of weather variance.